Characterization of adverse drug reactions causing admission to an intensive care unit (2017)
Aims: This study aimed to determine the occurrence of adverse drug reactions (ADRs) that caused admission to the intensive care unit (ICU) of a university hospital. Methods: Clinical records were reviewed for patients meeting the inclusion criteria who were admitted to the ICU between September and December 2012. Suspected cases of ADRs were documented. Nine researchers later evaluated causality using the Naranjo Algorithm, preventability using the Schumock and Thornton criteria, and clinical classification based on the dose–time–susceptibility system. Results: In total, 96 patients presented 108 cases of ADR (13.8%, 95% confidence interval 11.2–16.4%) as the cause of admission. The most frequent ADRs were bradyarrhythmias and upper gastrointestinal bleeding (12%). Therapeutic failure accounted for 20%. The most commonly associated medications were acetylsalicylic acid (16%) and losartan (10%). Forty-six cases were categorized as possible, and only one as definite. According to the dose–time–susceptibility classification, in 82% of the cases, the dosage was collateral (within the therapeutic range), and 90% were independent of time; the factors most associated with susceptibility to ADRs were comorbidities (42%) and age (49%). Forty-four percent of the ADRs were considered possibly preventable. Conclusions: ADRs contribute significantly to ICU admissions, and a significant number of ADRs are preventable. National studies are needed to assess their incidence and to establish classification standards to reduce their clinical impact. © 2016 The British Pharmacological Society